Comparative study on the mechanical and thermal properties of polycarbonate composites reinforced by KH570/SA/SDBS modified wollastonite fibers. Issue 11 (20th August 2022) - Chen, Feng; Bao, Yongzhong; Zhang, Jiamin; Yang, Ming; Ruan, Min; Feng, Wei; Jiang, Yufeng; Li, Ming; Chen, Yue
Abstract: In order to increase the applicability of wollastonite (Wo) in polycarbonate (PC) polymer, surface modification of Wo was carried out using different modifiers containing silane coupling agent KH570, stearic acid (SA), and sodium dodecylbenzene sulfonate. The physical, physic‐chemical, and application properties of modified Wo were evaluated. Results showed that KH570 modified Wo had narrower particle size distribution, higher absolute zeta potential and were more evenly distributed. Scanning electron microscope study confirmed their changes in morphology and aspect ratio during the modification process. The tensile strength of Wo/PC composites, in which KH570‐modified Wo was used were superior to those in which original Wo or other modifiers modified samples were used. The maximum tensile strength of 65 ± 1 MPa was obtained by adding 15 wt% KH570‐modified Wo. Thermal analysis indicated that adding Wo to the polycarbonate increased the residue content but decreased the thermal decomposition temperature and glass transition temperature slightly, regardless of unmodified or modified Wo. These results indicated that the well‐modified Wo mineral had the potential to replace expensive carbon and glass fibers as fillers in polycarbonate products. Abstract : Surface modification of wollastonite (Wo) was carried out using different modifiers containing silane coupling agent KH570, stearic acid, and sodium dodecylbenzene sulfonate. KH570‐Wo filled polycarbonate exhibited the maximum tensile strength of 65 ± 1 MPa. Wo increased residue but decreased decomposition rate and temperature slightly.